A retrospective audit of insulin infusion management involving a locally developed dynamic insulin infusion guideline in a tertiary ICU. Issue 3 (August 2015) - Breeding, Jeff; Welch, Susan; Buscher, Hergen; Nair, Priya; Frost, Carmen; Newman, Sally; Whittam, Susan
Abstract: Background: The ideal target blood glucose range for intensive care patients on insulin infusions is controversial. Avoidance of hyperglycaemia and hypoglycaemia are well supported goals. Methods: An audit of insulin infusion management was conducted following the institution of an insulin infusion guideline in a tertiary adult intensive care unit (ICU). The primary aim was to evaluate this guideline for safety and efficacy. Secondary aims were to compare outcomes such as ICU and hospital mortality, rate of severe hypoglycaemia, length of time within target zones, length of stay in ICU and hospital, ventilator hours and use of renal replacement therapy. Data analysis involved descriptive statistical techniques to allow comparison with other reported outcomes. Results: Thirty-eight (38) patients were included, representing 137 days of insulin infusions and 2537 blood glucose readings. The mean insulin infusion treatment time was 86.4 h (sd ±86.4), median 48 h (IQR 14.4–141.6). The mean insulin dose per day was 97.6 units (sd ±115.7), with a median of 68.7 (IQR 38.9–108.3). Blood glucose level (BGL) readings were within the desired target (6–9 mmols/L) and/or the buffer zones (4–6 and 9–12 mmols/L), 92.3% of the time. There were no episodes of severe hypoglycaemia (BGL ≤ 2.2 mmols/L). The median length of ICU stay was 5.9 days. Eighty-four (84) % of the cohort received mechanical ventilation and 26% received renal replacement therapy. The mean ventilation and renal replacement duration were days 6.9 and 9.4 days, respectively. The ICU and hospital mortality was 13.2% and 18.4%, respectively. Conclusion: The use of this locally developed insulin infusion guideline for hyperglycaemia within this ICU appears safe and effective. When compared to related published randomised controlled trials, the outcomes of this small scale single centre retrospective audit appear congruent. It achieved a severe hypoglycaemic rate of zero, with BGLs within target and buffer zones greater than 90%. It may be worthwhile for intensive care units to consider evaluating their own locally developed insulin infusion guidelines to ensure safety and efficacy.